COOLING METHOD OF SILUMINA CASTINGS AK15M3 AT VERTICAL CENTRIFUGAL CASTING - V. Yu. Stecenko; K. N. Baranov; A. P. Gutev (Литьë и металлургия)
The way of cooling of castings from silumin AK15M3 is developed at the vertical centrifugal casting, enabling to receive bimetallic blanks with high-disperse eutectic and hypereutectic microstructures and minimal allowance for machining.